Community organizing building social capital as a development strategy - Gittell, Ross J., 1957-; Vidal, Avis.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 1998)
Providing new insight into an important community development challenge, this text looks at how to stimulate the formation of community-based organizations and effective citizen action in neighbourhoods.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Community development -- United States -- Case studies; Community development corporations -- United States -- Case studies; Community organization -- United States -- Case studies; Social capital (Sociology); Electronic books